Reforming Federal Habeas Review of Military Convictions: Why AEDPA Would Improve the Scope and Standard of Review - Chapman, John K. (2004)
The writ of habeas corpus is a collateral remedy available to prisoners who have exhausted all available appellate remedies. Habeas corpus, which literally means to have or produce the body, involves a court order directing the custodian of a prisoner to bring the prisoner before the court in order to assess the validity of the prisoner's confinement. The importance of habeas corpus in the federal system has been recognized since the drafting of the Constitution and its historical roots trace back as far as the 12th Century in England. It is a procedure designed to protect individuals by forcing the government to always be accountable to the judiciary for a man's imprisonment. Under our constitutional framework, the courts established pursuant to Article III of the United States Constitution ( federal courts ), through the writ of habeas corpus, provide independent review of constitutional claims of error from both state and military convictions. When a federal court reviews a petition for a writ of habeas corpus from either a state or military conviction, it almost always reviews questions of fact or law that have been previously litigated in the original judicial system. The extent of federal review of the merits of a claim is a product of both the scope of review-the range of issues cognizable on review-and the standard of review-the level of deference accorded to the original judicial system's determination of the issue. Expanding the scope of review or decreasing the deference in the standard of review has the effect of increasing a federal court's ability to review determinations of the original judicial system, since restrictions on the federal courts' ability to review have been removed. The standard and scope of review applied by a federal court implicate two types of competing policy considerations, which I shall refer to as individual policy considerations and institutional policy considerations. Increased federal review, either through a broadened scope of review and/or a less deferential standard of review, furthers individual policy considerations, such as the protection of individual liberties. At the same time, however, increased federal review undermines institutional policy considerations, such as the autonomy of the original judicial system. Determining the proper standard and scope of review, and, by extension, the proper level of federal review of habeas petitions, involves striking a balance between these individual and institutional policy considerations